2014
DOI: 10.3109/02713683.2013.879596
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Functional Loss Associated with Ganglion Cell Complex Thinning between Patients with Glaucoma and Postoperative Macular Hole

Abstract: The thinning of the GCC affects the RGC function in the macula area differently for patients with OAG and patients after MH closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…These changes are similar to those obtained for the PhNR of the focal macular ERGs. 13,14,17,25,26 This indicates that the origin of the N2 of the slowsequence mfERG is the same as that of the PhNR of the focal macular ERG. Based on evidence obtained from experimental and clinical researches, the PhNR of the focal macular ERG originates from the neural activity of RGCs in the macular area.…”
Section: N2 In Central Area Corresponds To Phnr Of Focal Macular Ergsmentioning
confidence: 83%
See 1 more Smart Citation
“…These changes are similar to those obtained for the PhNR of the focal macular ERGs. 13,14,17,25,26 This indicates that the origin of the N2 of the slowsequence mfERG is the same as that of the PhNR of the focal macular ERG. Based on evidence obtained from experimental and clinical researches, the PhNR of the focal macular ERG originates from the neural activity of RGCs in the macular area.…”
Section: N2 In Central Area Corresponds To Phnr Of Focal Macular Ergsmentioning
confidence: 83%
“…Based on evidence obtained from experimental and clinical researches, the PhNR of the focal macular ERG originates from the neural activity of RGCs in the macular area. 13,14,17,[25][26][27] Thus, the N2 component of the mfERGs recorded from the central area represents the RGC activity of the corresponding retinal area.…”
Section: N2 In Central Area Corresponds To Phnr Of Focal Macular Ergsmentioning
confidence: 99%
“…It would be interesting to compare ganglion cell complex map including RGC cell bodies [ 35 ] among the groups after MH surgery. It has been reported that the GCC thickness is reduced after macular hole surgery [ 36 38 ].…”
Section: Discussionmentioning
confidence: 99%